Studi Komparasi Pemikiran Yusuf Qordhowi dan Ali Yafie Tentang Pertanggungjawaban Pelaku Pembuangan Limbah Cair Usaha Pencucian Kendaraan Bermotor - Muhammad Fajrul Falah (Journal of Islamic Business Law, 2018)
This research aims to analyze the accountability for perpetrators of waste disposal on the washing of motor vehicles by the method of comparison studies between Yusuf Qordhowi and Ali Yafie. This research uses the yurudis-normative approach to research methods by using libraries (Library research) and using the method of approximation of legislation (the statute approach). As for the source of the material law legal materials consist of primary, secondary and tertiary. Legal materials collection method using books and documentation relevant to the research. After going through the analysis of the thought of the two scholars obtained some results, namely: the difference of accountability against perpetrators of the disposal of liquid waste in safeguarding the environment, according to Yusuf Qordhowi is to use the five concepts mashlahat i.e. keep religion, soul, intellect, lineage and property, thus the maintenance and preservation of the environment is equal to the refinement of the goals of legislation. Does away with the thought of Ali Yafie i.e. always keeps the relationship between man and God, man with man and man with nature. As for the equation of liquid waste disposal offender accountability in maintaining the environment between the two scholars is located on the object if the Yusuf Qordhowi touch down between man and the surrounding environment while Ali Yafie and above the relationship of man with God. This research aims to analyze the accountability for perpetrators of waste disposal on the washing of motor vehicles by the method of comparison studies between Yusuf Qordhowi and Ali Yafie. This research uses the yurudis-normative approach to research methods by using libraries (Library research) and using the method of approximation of legislation (the statute approach). As for the source of the material law legal materials consist of primary, secondary and tertiary. Legal materials collection method using books and documentation relevant to the research. After going through the analysis of the thought of the two scholars obtained some results, namely: the difference of accountability against perpetrators of the disposal of liquid waste in safeguarding the environment, according to Yusuf Qordhowi is to use the five concepts mashlahat i.e. keep religion, soul, intellect, lineage and property, thus the maintenance and preservation of the environment is equal to the refinement of the goals of legislation. Does away with the thought of Ali Yafie i.e. always keeps the relationship between man and God, man with man and man with nature. As for the equation of liquid waste disposal offender accountability in maintaining the environment between the two scholars is located on the object if the Yusuf Qordhowi touch down between man and the surrounding environment while Ali Yafie and above the relationship of man with God.